Reflections on the 2025 GASC Conference in Warsaw… and the Originary Hypothesis - Gans, Eric Lawrence (2025)
Ainsi mourut la fille d’Hamilcar pour avoir touché au voile de Tanit. Thus did Hamilcar’s daughter perish for having touched the veil of Tanith. Gustave Flaubert, Salammbô (1862) This year’s conference, whose cultural bonuses included a ballet and a Chopin concert, as well as a visit to Warsaw’s recently opened National Library Museum, went off...